Dynamic metabolic solutions to the sessile life style of plants. Issue 11 (16th October 2018) - Knudsen, Camilla; Gallage, Nethaji Janeshawari; Hansen, Cecilie Cetti; Møller, Birger Lindberg; Laursen, Tomas
Abstract : Plants are sessile organisms. To compensate for not being able to escape when challenged by unfavorable growth conditions, pests or herbivores, plants have perfected their metabolic plasticity by having developed the capacity for on demand dynamic biosynthesis and storage of a plethora of phytochemicals. Abstract : Covering: up to 2018 Plants are sessile organisms. To compensate for not being able to escape when challenged by unfavorable growth conditions, pests or herbivores, plants have perfected their metabolic plasticity by having developed the capacity for on demand synthesis of a plethora of phytochemicals to specifically respond to the challenges arising during plant ontogeny. Key steps in the biosynthesis of phytochemicals are catalyzed by membrane-bound cytochrome P450 enzymes which in plants constitute a superfamily. In planta, the P450s may be organized in dynamic enzyme clusters (metabolons) and the genes encoding the P450s and other enzymes in a specific pathway may be clustered. Metabolon formation facilitates transfer of substrates between sequential enzymes and therefore enables the plant to channel the flux of general metabolites towards biosynthesis of specific phytochemicals. In the plant cell, compartmentalization of the operation of specific biosynthetic pathways in specialized plastids serves to avoid undesired metabolic cross-talk and offers distinct storage sites for molar concentrations of specific phytochemicals. Liquid–liquid phase separation may lead to formation of dense biomolecular condensates within the cytoplasm or vacuole allowing swift activation of the stored phytochemicals as required upon pest or herbivore attack. The molecular grid behind plant plasticity offers an endless reservoir of functional modules, which may be utilized as a synthetic biology tool-box for engineering of novel biological systems based on rational design principles. In this review, we highlight some of the concepts used by plants to coordinate biosynthesis and storage of phytochemicals.